Evaluation of the diagnostic and management accuracy of closed fractures of forearm and wrist using validated vignettes as a reference standard by emergency centre clinicians in the Cape Town metropole - Goncalves, Melisanda (Division of General Surgery, 2021)
Introduction Reduction of forearm and wrist fractures is a common practice in the Emergency Centre (EC). EC doctors must be familiar with the appropriate management thereof. The standard treatment of a fracture involves reduction and immobilization. This study aims to describe the diagnostic and management accuracy of EC clinicians using validated vignettes (also used as the reference standard) of adult patients with closed fractures of the forearm or wrist. Methods This is a prospective, cross-sectional study in the form of an electronic questionnaire to address the study aim. A set of vignettes were created and then validated to serve as the control for the study participants. The study was open to emergency medicine consultants, emergency medicine trainees/registrars, medical officers, and community service medical officers employed at a secondary-level public hospital EC in the Cape Town metropole. Comparison is made by the number and proportions of correct and incorrect answers using the vignette reference standard. Data were analysed using ChiSquare (X2). Results For the diagnosis of forearm and wrist fractures, EC clinicians present 86,8% (1309/1508) correct responses (p=0.68) and, for the course of action, 78% (278/354) correct responses (p=0.09). For the overall management of the fractures (diagnostic and course of action), EC clinicians answered correctly to 84,9% (1585/1866) and incorrectly to 15,1% (281/1866), although the difference by each EC clinician group.was not significant (p=0.72). Conclusion In Western Cape, EC doctors appear to fare better than reported in the literature. However, this can not be shown definitively with this dataset. Regular training is necessary for all clinicians working in EC to improve their skills in managing forearm and wrist fractures, including the interpretation of X-ray imaging. Clear and good notes in the patient folder, top-quality X-ray images, good EC work environment, and improvement between doctors communication are other sets of requirements important to help to avoid errors in fracture management.